2019
DOI: 10.1186/s12978-019-0831-5
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of community elders’ perceptions about the underutilization of formal maternal care and maternal death in rural Nigeria

Abstract: BackgroundUnderutilization of formal maternal care services and accredited health attendants is a major contributor to the high maternal mortality rates in rural communities in Nigeria. Perceptions of a poor quality of care and inaccessible services in health facilities strongly influence the low use of formal maternal care services. There is therefore a need to understand local perceptions about maternal health services utilization and maternal death. This study thereby aims to explore perceptions and beliefs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 78 publications
0
25
0
Order By: Relevance
“…The implication is that CCT was a good motivating factor for some women. It undoubtedly took care of some financial barriers which are a major reason for poor health-seeking behavior especially among rural residents in SSA (34)(35)(36) as well as the opportunity cost of being away from income-generating activities during a healthcare-seeking time (3,37). Since the incentive was paid post-behavior, those motivated by the CCT had to have some prior resources that allowed them to perform the desired behavior (e.g., pay for transport) before collecting the money weeks or months later.…”
Section: Discussionmentioning
confidence: 99%
“…The implication is that CCT was a good motivating factor for some women. It undoubtedly took care of some financial barriers which are a major reason for poor health-seeking behavior especially among rural residents in SSA (34)(35)(36) as well as the opportunity cost of being away from income-generating activities during a healthcare-seeking time (3,37). Since the incentive was paid post-behavior, those motivated by the CCT had to have some prior resources that allowed them to perform the desired behavior (e.g., pay for transport) before collecting the money weeks or months later.…”
Section: Discussionmentioning
confidence: 99%
“…The research took place in the Eastern Region of Ghana, a primarily rural region, with nearly two-thirds of the population of 2,106,696 residing in rural areas. 19 The primary industry is agriculture, followed by wholesale or retail trade. 19 The most common type of home is constructed of mud entailing one to two rooms.…”
Section: Research Settingmentioning
confidence: 99%
“…19 The primary industry is agriculture, followed by wholesale or retail trade. 19 The most common type of home is constructed of mud entailing one to two rooms. 19 The Region is divided into 26 administrative districts.…”
Section: Research Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…In assessing the use of PHCs for skilled pregnancy care, our team conducted initial formative research that showed that less than 47% of pregnant women in rural Edo used any of the available PHCs for care 16. We further ascertained through mixed qualitative research that these were due to perceptions relating to poor-quality services, high-cost of services, poor roads and transportation difficulty, gender and cultural issues and perceptions that PHCs may not be the appropriate places for women to receive antenatal and delivery care 10 17–19. To address these concerns, we worked with leaders in 20 communities in the area in collaboration with policymakers, sector planners and other stakeholders to design interventions to address the bottlenecks identified as preventing the use of skilled care by pregnant women in the communities.…”
Section: Introductionmentioning
confidence: 99%